Race-specific associations of 25-hydroxyvitamin D and parathyroid hormone with cardiometabolic biomarkers among US white and black postmenopausal women. Issue 2 (29th May 2020) - Xia, Jin; Tu, Wanzhu; Manson, JoAnn E; Nan, Hongmei; Shadyab, Aladdin H; Bea, Jennifer W; Cheng, Ting-Yuan D; Hou, Lifang; Song, Yiqing
ABSTRACT: Background: Concentrations of 25-hydroxyvitamin D [25(OH)D] tend to be lower in African Americans than in non-Hispanic whites, but whether adding information on parathyroid hormone (PTH) can help explain the higher cardiometabolic risk among African Americans is unknown. Objectives: This study examined race (black/white)-specific independent and joint associations of 25(OH)D and PTH with cardiometabolic biomarkers including high-sensitivity C-reactive protein (hs-CRP), estimated glomerular filtration rate (eGFR), and homeostasis model assessment of insulin resistance (HOMA-IR) and β-cell function (HOMA-B). Methods: Among 1500 white and 1300 black postmenopausal women without cardiovascular disease from the Women's Health Initiative Observational Study, a weighted linear regression analysis and a novel penalized spline-based semiparametric model with contour plots, accounting for possible nonlinear relations and interactions simultaneously, were used to investigate the race-specific independent and joint associations of 25(OH)D and PTH with each biomarker. Results: Black women had lower concentrations of 25(OH)D and higher PTH, HOMA-IR, HOMA-B, hs-CRP, and eGFR than white women (all P values < 0.0001). Lower 25(OH)D and higher PTH were each independently and jointly associated with higher HOMA-IR in both white and black women, whereas a similar joint relation with HOMA-B was observed in white women only. In contrast, PTH was nonlinearly associated with HOMA-B in black women and positively associated with hs-CRP in white women, independently of 25(OH)D. Whereas there was an inverse linear relation between PTH and eGFR in white women after accounting for 25(OH)D, PTH and 25(OH)D were jointly and nonlinearly associated with eGFR in black women. Conclusions: We found that the joint association of 25(OH)D and PTH with β-cell function, systemic inflammation, and kidney function apparently differed between white and black women. Further studies are needed to determine whether differences in the vitamin D–PTH endocrine system contribute to racial disparities in cardiovascular health.